CHIRPS-Based Spatio-Temporal Rainfall Analysis as a Basis for Evaluating Cropping Pattern Suitability in Coastal West Sumatra - Nugraha Ramadhan; Indra Dwipa; Muhsanati Muhsanati; Winda Purnama Sari; Afrima Sari; Salsabila Amanda; Danang Nugroho; Rezky Devo Ramadhan; Rizky Armei Saputra (Journal of Applied Agricultural Science and Technology, 2026)
Rainfall variability, in terms of amount, distribution, and timing, can increase the risk of crop failure and reduce crop yields. This study aims to analyze CHIRPS (Climate Hazards Group InfraRed Precipitation with Stations) rainfall dynamics across several coastal areas of West Sumatra and to evaluate agroclimatic zones to assess the suitability of climate-adaptive cropping patterns. Monthly rainfall data for the period 1995-2024 were analyzed using the IDW interpolation method to produce rainfall distribution maps. This study also classified agroclimatic zones using Oldeman's classification to assess the suitability of cropping patterns. The analysis showed significant annual rainfall fluctuations, with high rainfall dominating the 1995-2014 period and a decline in the 2015-2024 period. Changes in monthly rainfall patterns, particularly the increase in rainfall from March to May during the 2015-2024 period, may affect planting times and irrigation management. The three regions studied (Padang Pariaman, Pariaman, and Padang) are in climate zone A1, with more than 9 consecutive wet months, allowing year-round rice cultivation. However, rainfall fluctuations require adjustments in planting timing and the selection of secondary crops that are more drought-resistant. The results of this study provide a stronger basis for agricultural planning that is more adaptive to climate change, with recommendations for adjustments to the planting calendar and irrigation management to ensure the sustainability of efficient and sustainable agricultural production.